2021
DOI: 10.1016/j.jacbts.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Clec4e-Receptor Signaling in Myocardial Repair After Ischemia-Reperfusion Injury

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…They found upregulation of genes associated with the immune response, which correlated inversely with estimated glomerular filtration rate. Several of the differentially expressed genes in their study were also identified in our analysis, most notably including CC‐chemokine ligand 19 ( Ccl19 ) and its receptor 7 ( Ccr7 ), which are essential in establishing dendritic cell and T cell recruitment 44 ; several members of the C‐type lectin family (eg, Clec5a , Clec7a ), which have been strongly linked with activation of the nucleotide‐binding oligomerization domain‐like receptor protein 3 inflammasome and pyroptotic cell death 23 , 24 ; SLAM family member 6 ( Slamf6 ) and glycoprotein CD2 ( Cd2 ), both of which belong to the immunoglobulin superfamily and are expressed on natural killer, T, and B lymphocytes 45 ; interferon regulatory factor 4 ( Irf4 ), which has been implied in kidney fibrosis as it may regulate the migration and activation of macrophages 46 ; surface receptor sialic acid binding Ig‐like lectin 1 ( Siglec1 ), which regulates monocyte–macrophage activation and has been linked to increased frequency of kidney complications in patients with systemic lupus erythematosus 47 ; and members of the matrix metalloproteinase family (eg, Mmp2 , Mmp7 , MMp12 ), which play and important role in the degradation of the extracellular matrix and have been linked to CKD progression. 48 These findings are also well in accordance with the study by Tajti et al, 39 who confirmed the role of inflammation across a wide spectrum of CKD entities.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…They found upregulation of genes associated with the immune response, which correlated inversely with estimated glomerular filtration rate. Several of the differentially expressed genes in their study were also identified in our analysis, most notably including CC‐chemokine ligand 19 ( Ccl19 ) and its receptor 7 ( Ccr7 ), which are essential in establishing dendritic cell and T cell recruitment 44 ; several members of the C‐type lectin family (eg, Clec5a , Clec7a ), which have been strongly linked with activation of the nucleotide‐binding oligomerization domain‐like receptor protein 3 inflammasome and pyroptotic cell death 23 , 24 ; SLAM family member 6 ( Slamf6 ) and glycoprotein CD2 ( Cd2 ), both of which belong to the immunoglobulin superfamily and are expressed on natural killer, T, and B lymphocytes 45 ; interferon regulatory factor 4 ( Irf4 ), which has been implied in kidney fibrosis as it may regulate the migration and activation of macrophages 46 ; surface receptor sialic acid binding Ig‐like lectin 1 ( Siglec1 ), which regulates monocyte–macrophage activation and has been linked to increased frequency of kidney complications in patients with systemic lupus erythematosus 47 ; and members of the matrix metalloproteinase family (eg, Mmp2 , Mmp7 , MMp12 ), which play and important role in the degradation of the extracellular matrix and have been linked to CKD progression. 48 These findings are also well in accordance with the study by Tajti et al, 39 who confirmed the role of inflammation across a wide spectrum of CKD entities.…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, periostin ( Postn ) and several members of the C‐type lectin family (eg, Clec5a , Clec7a ) were included in this cluster, the former of which has been linked to myocardial fibrosis 22 and the latter of which has been strongly linked with activation of the nucleotide‐binding oligomerization domain‐like receptor protein 3 inflammasome and pyroptotic cell death in the pathophysiology of myocardial infarction. 23 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, rsad2 , an interferon (IFN)-stimulated gene (126), was up-regulated (Figure 4B; D1). These enriched genes suggest that Neu 2 exhibits functions related to inflammatory propagation and recruitment of more inflammatory cells in non-regenerative condition (Figure 4A and Figure 4-figure supplement 1B) (127, 128). Both neutrophil clusters Neu 1 and Neu 2 expressed genes relative to energy metabolisms, regulation of proteolysis, and autophagy (Figure 4B; D6).…”
Section: Resultsmentioning
confidence: 98%
“…These enriched genes suggest that Neu 2 exhibits functions related to inflammatory propagation and recruitment of more inflammatory cells in non-regenerative condition (Figure 4A and Figure 4-figure supplement 1B) (127,128). Both neutrophil clusters Neu 1 and Neu 2 expressed genes relative to energy metabolisms, regulation of proteolysis, and autophagy (Figure 4B; D6).…”
Section: Dynamic Cell Proportion Analyses Of Inflammatory Cell Cluste...mentioning
confidence: 93%
“…High-throughput technologies have been further developed to integrate omics data for the identification of causal genes and molecular mechanisms involved in the development of cardiovascular events. These techniques were applied both in mice, enhancing our understanding about the differential cell function across tissues [ 32 , 33 , 34 ], and in humans, taking advantage of the large consortia, autopsy evidence and imaging techniques [ 35 , 36 , 37 , 38 ].…”
Section: Multi-omics Tools For Cardiovascular Risk Prediction Tools: Transcriptomic and Epigenetic Markersmentioning
confidence: 99%